A review of the application of Next Generation Sequencing (NGS) in wild terrestrial vertebrate research - Annavi, Geetha; Uli, Joey Ee; Arumugam, Ramitha (ScienceDomain International, 2019)
In era of sequencing revolution, scientists seek for knowledge about the ever-expanding field of technology, Next Generation Sequence (NGS) to be applied in their research due to its high reliability and rate of discovery. What is NGS? To obtain a detailed understanding about NGS, it is required to look back the history of sequencing and how the NGS stepped into life science. This review paper gives an overview of NGS projects in wild terrestrial vertebrate including applications such as whole genome sequencing and metagenomics.